Risk Factors Associated with Coronary Artery Disease in Gaza (Global Journal of Medical Research, 2016)
Aim: Coronary Artery Disease (CAD) is considered the most life threating disease in the world. Our study aims to estimate the association of lipid profile, other risk factors with CAD development. Method: Blood samples were taken from cross-sectional sample (n=94) of CAD inpatients (68 males and 26 females) recorded at the period of 1/6/2008 to 16/8/2008 at El-shefaa hospital of Gaza. The patient history of age, sex, BMI, diabetic, hypertension, smoking, physical activity, stress, working and family history were collected by questionnaire, hospital administration and nursing data in coordination with the Department Physicians. We have conducted this study on hospitalized Palestinian CAD patients. Results: the percentage of gender were (72.3%) males and (27.7%) females, the mean patients age was 57.3 yrs. within range (45 #x2013; 66 yrs.). the means of serum cholesterol, triglyceride (TG) and Low Density Lipoprotein (LDL) were lowered and closed to international ranges, unlike High Density Lipoprotein (HDL) level. In addition, the distribution of Sedentary Physical Activity was the highest CAD risk factor, particularly females were higher than males (P=0.001), male smokers were the second highest risk factor and the stressed females were the third highest risk factor (P=0.001). In addition, we noticed the total cholesterol/HDL ratio is higher indicator than LDL/HDL and HDL/LDL ratio. Conclusion: the means of cholesterol, TG, LDL and HDL were low and close to international ranges, while, the distribution of Sedentary Physical Activity of females, male smokers and the stressed females were the highest risk factors. All of those results are depend on genetic factors, life style and nutrition in our area. In addition, we noticed the total cholesterol/HDL ratio is most effective CAD indicator.
Keywords: low density lipoprotein; high density lipoprotein; serum cholesterol; coronary artery disease